2018
DOI: 10.1007/s00405-018-5076-3
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic sinusitis involving the frontal sinus: is middle meatal antrostomy enough?

Abstract: 2B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…15,31,32 This study showed that the anterior sinus was the most involved area in maxillary sinusitis, followed by the frontal sinus. 23 For the severity of chronic rhinosinusitis on CT, patients with oroantral fistula showed significantly improved CT findings after tooth extraction. One possible reason could be additional irrigation through the Schneiderian membrane during extraction.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…15,31,32 This study showed that the anterior sinus was the most involved area in maxillary sinusitis, followed by the frontal sinus. 23 For the severity of chronic rhinosinusitis on CT, patients with oroantral fistula showed significantly improved CT findings after tooth extraction. One possible reason could be additional irrigation through the Schneiderian membrane during extraction.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, most of the previous studies on treatment for odontogenic maxillary sinusitis were limited reports from small populations. 13,23 Thus, in this study, we sought to propose a management policy from our clinical experience.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-nine studies reported specific diagnostic criteria 7,10,1662 and 14 studies did not report any diagnostic criteria (either original or referenced) for OS. 8,11,6374 It should be noted that four articles 10,21,31,39 were retrospective radiological analyses and provided radiologic diagnostic criteria only.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, patients with severe symptoms or orbital/intracranial complications should be treated with a combined approach right from the diagnosis, thus allowing for sinus drainage and resolution of the etiological dental focus. While endoscopic sinus surgery has an undebated role in ODS treatment, the extent of said surgery is still a matter of debate, since some authors 19,20 proposed that middle antrostomy is enough to warrant patient healing. While prospective validation of these approaches is required, at present opening all sinuses involved in ODS [21][22][23] , while being the most frequent approach, is recommended only in case of ODS with orbital or intracranial complications 9 .…”
Section: General Principles Of Ods Treatmentmentioning
confidence: 99%